2021
DOI: 10.4018/ijer.20210101.oa5
|View full text |Cite
|
Sign up to set email alerts
|

The Rise of eSports

Abstract: The availability and affordability of increased Internet bandwidth, video memory, and processing speed has enabled Electronic sports (eSports) to become a flourishing global sensation and college students are helping to drive this phenomenon. This mixed-methods study focuses on feedback from 159 college students regarding the eSports phenomenon across both gender and educational classification. Findings from the study include their eSports-related gaming and spending habits, and perceptions of personal and aca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…China accounts for $2.9 Billion of funding, followed by the U.S with $1.7 Billion. The result presented in Table 4 represents a plausible picture of the eSports funding geographical distribution with APAC being the market leader, as described in several industry reports (NewZoo, 2020;Deloitte, 2019;Goldman Sachs, 2018). The results are in line with academic research on regional variations of VC funding (Colombo et al, 2019;Hege et al, 2009), suggesting that the sample is not biased or overrepresenting American companies.…”
Section: Data and Summary Statisticssupporting
confidence: 61%
See 1 more Smart Citation
“…China accounts for $2.9 Billion of funding, followed by the U.S with $1.7 Billion. The result presented in Table 4 represents a plausible picture of the eSports funding geographical distribution with APAC being the market leader, as described in several industry reports (NewZoo, 2020;Deloitte, 2019;Goldman Sachs, 2018). The results are in line with academic research on regional variations of VC funding (Colombo et al, 2019;Hege et al, 2009), suggesting that the sample is not biased or overrepresenting American companies.…”
Section: Data and Summary Statisticssupporting
confidence: 61%
“…3 New monetization opportunities are attracting the interest of traditional investors, among which venture capital funds (VC) are playing a key-role (Goldman Sachs, 2018). Indeed, the level of funding provided by investors to eSports firms has seen a strong growth globally with $4.5 billion invested in 2018, as well as 103.1% growth delivered between 2014 and 2018, and investors expect to see this steadily increasing (Deloitte, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…By 2019, the Newzoo industry report revealed that the number of global audiences for eSports was 443 million, and the industry made USD 950 million [8]. Other reports have anticipated a USD 1.79 billion industry for 2022, with high expectations to be part of future Olympic games [9]. eSports, or electronic sports, can be introduced as a new form of sports, where digital games are played on any platform, online or offline, individually and/or as a team [10].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike when playing other video games, the participants believed that eSports enhanced their body coordination, including brain-eye-hand coordination, because it required acting and reacting by pressing directional keys and the mouse rapidly and strategically. In terms of cognition, playing eSports enhanced the middle-aged and older adults' attentiveness and strategic thinking by motivating them to solve problems or think outside the box while playing games [26]. Moreover, keeping the mind engaged in cognitively demanding activities is essential for enhancing memory function in older adults [27].…”
Section: Behavioral Beliefsmentioning
confidence: 99%